Silver nanoparticles of variable morphology synthesized in aqueous foams as novel templates - Mandal, Sujata; Arumugam, S. K.; Pasricha, R.; Sastry, M. (Bulletin of Materials Science, 2005)
In this paper, we describe the synthesis of silver nanocrystals within aqueous foams as a template More specifically, we show that aqueous Ag+ ions may be electrostatically complexed with the anionic surfactants aerosol OT (sodium bis-2-ethylhexyl-sulfosuccinate, (AOT) and sodium dodecyl sulphate (SDS)) in a highly stable liquid foam. After drainage of the foam, the silver ions are reduced in situ by introducing sodium borohydride into the foam by capillary flow. This leads to the formation of silver nanoparticles of spherical, tape- and sheet-like morphology in the foam. The structure of the foam is extremely complex and presents reaction sites of different spatial extent. The differences in foam reaction-site geometry are believed to be responsible for the morphology variation in the silver nanoparticles observed. The silver nanoparticles are observed to be extremely stable in solution suggesting that the AOT or SDS molecules stabilize them. This approach appears promising for application in large-scale synthesis of nanoparticles and may be readily extended to other chemical compositions.
Keywords: Chemical synthesis; composites; foam; Intercalation; Nanoparticles